Why gender-sensitive social protection is critical to the COVID-19 response in low- and middle-income countries - Hidrobo, Melissa; Kumar, Neha; Palermo, Tia; Peterman, Amber; Roy, Shalini (International Food Policy Research Institute, 2020)
The COVID-19 pandemic presents an opportunity to address existing gender inequalities through social protection. Program designs should be adjusted to account for gender, in a manner informed by existing analysis, while taking a long-term approach. Related issues of political economy, coordination, and financing that have gender considerations should be explored in future guidance. Because these are complex issues and unintended consequences of programming are possible, more research is needed on intersections of social protection, gender and pandemics, where ethically feasible. At a minimum, monitoring statistics should be sex- and age-disaggregated and, where possible, data should be collected to ensure risks to beneficiaries do not increase. Taken together, these policy adjustments and new evidence can lay the groundwork for more gender-sensitive social protection systems in LMICs both during the crisis and beyond.